Stakeholder Management in the Development of Building Organizations - Komelina, Olha; Hrynko, Olexandr; Khrystenko, Olena (International Journal of Engineering and Technology, 2018)
This article explored theoretical concepts of stakeholder management development and features of their usage in practical functioning of building organizations. There is a description of potential partners of these organizations.Also, the expediency of studying internal opportunities of communication system`s development is given, where important role belongs to management`s quality, by the criterion of evaluation ‘enterprise- consumer’.Within external stakeholders the role of state institutions is highlighted, which can be involved in realization of building projects on the basis of public-private partnership. Structural and functional way of the cooperation evaluation between building organization and its stakeholders is developed, we can consider it as a basis of requirements formation concerning creation of the building organization`s professional partnership performance.Moreover, we explain the importance of the strategic management in enterprise development considering technologies of stakeholder management was explained.